Palladium-Catalyzed Annulation of Acyloximes with Arynes (or Alkynes): Synthesis of Phenanthridines and Isoquinolines - Gerfaud, Thibaud; Neuville, Luc; Zhu, Jieping (Angewandte Chemie (International ed.), 2009)
Intermolecular insertion: A palladium‐catalyzed domino aminopalladation/ CH functionalization sequence has been developed, and provides access to functionalized phenanthridines and isoquinolines (see scheme; Tf=triflate, TMS=trimethylsilyl, M.S.=molecular sieves). The use of butyronitrile as the solvent is determinant to the success of the domino process.